Developing a Strategic Framework for Enhancing Employee Engagement and Retention - Yasmin, Kirana Erlinda; Bangun, Madju Yuni Ros; Ginting, Henndy (Journal of Management, Economic, and Financial, 2024)
Employee engagement is a critical focus in human resource management, particularly in industries with strategic significance such as the dairy industry in Indonesia. The Indonesian dairy industry plays a vital role in ensuring community nutrition and contributes significantly to the national economy through job creation and improving farmer welfare. As the market leader, PT Indosusu Nasional acknowledges that human resources are its primary asset and key to organizational success, while facing intense competition and high employee turnover. This study aims to analyze employee engagement at PT Indosusu Nasional, focusing on factors influencing engagement levels and their impact on employee retention. Data was collected through a survey involving employees from various departments of the company. The results in this study can be recommended to PT Indosusu Nasional as a strategy in retaining its employees are related to the company's reputation in building the company's image and conducting routine training for employees.